The impact of Amazonian deforestation on Amazon basin rainfall. Issue 21 (12th November 2015) - Spracklen, D. V.; Garcia‐Carreras, L.
Abstract: We completed a meta‐analysis of regional and global climate model simulations ( n  = 96) of the impact of Amazonian deforestation on Amazon basin rainfall. Across all simulations, mean (±1 σ ) change in annual mean Amazon basin rainfall was −12 ± 11%. Variability in simulated rainfall was not explained by differences in model resolution or surface parameters. Across all simulations we find a negative linear relationship between rainfall and deforestation extent, although individual studies often simulate a nonlinear response. Using the linear relationship, we estimate that deforestation in 2010 has reduced annual mean rainfall across the Amazon basin by 1.8 ± 0.3%, less than the interannual variability in observed rainfall. This may explain why a reduction in Amazon rainfall has not consistently been observed. We estimate that business‐as‐usual deforestation (based on deforestation rates prior to 2004) would lead to an 8.1 ± 1.4% reduction in annual mean Amazon basin rainfall by 2050, greater than natural variability. Key Points: Deforestation of the Amazon likely to lead to reductions in regional rainfall Current deforestation extent estimated to reduce annual rainfall across Amazon basin by 1.8% By 2050, deforestation estimated to reduce annual rainfall by 8.1%, greater than natural variability